True believer - Spark, Nicholas (London : Sphere, 2019)
Can the mysteries of the human heart ever be unravelled? Pursuing a scientific explanation for a disturbing and unexplained phenomenon, Jeremy's sceptical nature is thrown off course when he meets Lexie, the town librarian. As they work together, ghostly occurrences and passionate moments converge, forcing Jeremy to realise that there are some truths science cannot explain, as he finally appreciates the pleasures of exploring the heart.
Keywords: Journalists -- Fiction